Analisis Akar Penyebab Defect dan Lolosnya Produk Defect Proses Pendempulan Big Bus di PT.XYZ - Retno Wulan Damayanti; Ereika Ari Agassi (Performa: Media Ilmiah Teknik Industri, 2014)
PT.XYZ is a manufacturer of body bus which produce four type of bus that is big bus, medium bus, small bus, and mini bus. There is ten process to produce 1 unit big bus that is machine work, sub assembly, pra production, body assembly, metal finish, epoxy, putty, painting, trimming, and PDI (Pre Delivery Inspection). Based on the check sheet data summary from January to August of 2013, most major defect are in the putty process and based on the observation and interviews, there is product defects that pass inspection and entry process of painting. So, this study aims to identify the root cause of the defect and the escape of product defect from inspection. Root Cause Analysis method are used to identify the root cause of this problem. Using Root Cause Analysis method, RCA diagram showed that the root causes of defects are SOP that cannot be applied, the color of paint (epoxy) is less clear for inspection, poor lighting, lack of machinery, the wages of workers, and porous of fiber, while the root cause of the escape of product defect from inspection are SOP that cannot be applied, the color of paint (epoxy) is less clear for inspection, poor lighting, lack of machinery, the wages of workers, and lack of quality standards.